BMC Proceedings
BMC Proceedings is an online, open access journal publishing proceedings of conferences across all scientific and clinical disciplines, including peer-reviewed full-length articles, collections of abstracts and meeting reports. Devoted specifically to conference publications, including large collections of articles, meetings of specialized interest and conferences of a cross- or multi-disciplinary nature, each collection is published as a supplement.